Some Aspects of the Epidemiology and Diagnostics of Malignant Skin Neoplasms - V. V. Chebotarev; Z. R. Khismatullina; Y. A. Zakirova (Креативная хирургия и онкология, 2020)
This review article discusses important issues concerned with the epidemiology, classification and diagnosis of such widespread malignant skin neoplasms, as melanoma, basal cell carcinoma and squamous cell carcinoma. The relevance of these aspects is associated not only with a rapid increase in the incidence of malignant skin neoplasms, but also with the emergence of new, more accurate, methods for diagnosing such conditions. The use of non-invasive diagnostic tools can increase the accuracy of clinical diagnosis, thus allowing malignant skin tumours to be detected at early stages and the number of unreasonable surgical interventions to be reduced. A belated diagnosis of malignant skin tumours causes diagnostic errors and inadequate management tactics for patients with skin neoplasms. In this regard, timely identification of skin neoplasms should be treated as an interdisciplinary problem, the solution of which requires joint efforts of various medical specialists. The importance of correcting the existing classifications of malignant skin neoplasms and pre-cancers is highlighted, along with the development of regulations for their timely diagnosis and treatment.